SELF-PERCEPTION OF HAPPINESS IN WOMEN WITH BREAST CANCER - Magalhães, Maria Cristina Figueroa; Karvat, João Gabriel Vicentini; Lima, Jéssica Heloise Camargo de; Pasquini Neto, Ricardo (Mastology, 2026)
Objective: The aim of this study was to establish correlations between well-being and breast cancer (BC)-related aspects. Methods: Women with BC diagnosis (n=42) were interviewed and National Gross Happiness was assessed through an adaptation of the Second Gross National Happiness Survey Questionnaire. Cancer-related data were also assessed, such as staging, anatomopathological results, hormonal status, and surgical modality. Results: The mean age during BC diagnosis was 43.8 years. The overall happiness self-perception (HSP) score found was 8.8 out of 10. Unhappy feelings or deprived humor were reported by 61.8% of the interviewed women. Good doctor-patient relationship (DPR) during treatment was reported by 92.3% of the study population, and those who reported it had higher overall HSP scores in comparison with those who reported problems regarding their DPR. Besides, 97.6% of the interviewed women had surgical treatment, and our data showed no significant changes in the overall HSP scores among patients undergoing mastectomy and lumpectomy. Conclusion: Women with BC are prone to experience unhappiness and have deprived humor, despite having high overall HSP scores. Besides, in contrast to our original thoughts, the modality of surgical treatment did not have a significant impact on HSP scores.